2017
DOI: 10.1016/j.jip.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Response of three cyprinid fish species to the Scavenger Deterrent Factor produced by the mutualistic bacteria associated with entomopathogenic nematodes

Abstract: The symbiotic bacteria, Photorhabdus and Xenorhabdus associated with entomopathogenic nematodes (EPNs) in the genera Heterorhabditis and Steinernema, respectively, produce a compound(s) called the Scavenging Deterrent Factor (SDF). SDF deters a number of terrestrial insect scavengers and predators and one bird species from feeding on host insects killed by the nematode-bacterium complex but has not been tested against aquatic vertebrates. Moreover, the Heterorhabditis-Photorhabdus association is believed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
1
5
0
2
Order By: Relevance
“…Otro modelo importante de bacterias con actividad entomopatógena son Xenorhabdus y Photorhabdus, las cuales establecen relaciones mutualistas con nematodos de las familias Steinernema sp y Heterorhabditis sp respectivamente [41]. Ambos nematodos tienen ciclos de vida similares, y se divide en huevo, larva, estadios juveniles (J1, J2, J3, J4), y adultos, únicamente el tercer estadio juvenil (J3) de estos nemátodos son infectivos y buscan al hospedador, detectando sus excrementos y la producción de CO 2 [42].…”
Section: Nematodos Mutualistasunclassified
“…Otro modelo importante de bacterias con actividad entomopatógena son Xenorhabdus y Photorhabdus, las cuales establecen relaciones mutualistas con nematodos de las familias Steinernema sp y Heterorhabditis sp respectivamente [41]. Ambos nematodos tienen ciclos de vida similares, y se divide en huevo, larva, estadios juveniles (J1, J2, J3, J4), y adultos, únicamente el tercer estadio juvenil (J3) de estos nemátodos son infectivos y buscan al hospedador, detectando sus excrementos y la producción de CO 2 [42].…”
Section: Nematodos Mutualistasunclassified
“…Depending on the available resources, one or more EPN generations will occur within the cadaver, and a large number of infective juveniles are gradually released into environment for infecting other hosts and continuing their life cycle (Poinar, 1990). Since the defence system of the insect cadavers is completely lost, the symbiotic bacteria must then provide defences in order to avoid the loss of the EPN population inside the cadaver (Jones et al, 2016) from foraging insects ants (Zhou et al, 2012), cricket and wasps (Gulcu et al, 2012), beetles (Jones et al, 2017), bird (Fenton et al, 2011) and even fishes (Raja et al, 2016). However, besides the abovementioned predators, insect cadavers containing EPNs will also suffer risk of infection from entomopathogenic fungi, entomopathogenic bacteria and even competition with other soil free-living nematodes.…”
Section: Epbs Protect Infected Host Cadaversmentioning
confidence: 99%
“…A wide range of species, including various arthropods [ 166 , 167 ] and birds [ 168 ], are known to be sensitive to such factors, avoiding infected cadavers or promptly rejecting them after an attempt to consume them. Recently, laboratory tests on three cyprinid fish species showed they were also sensitive to SDFs, rejecting G. mellonella larvae killed by Heterorhabditis or Steinernema species, and preferentially feeding on freeze-killed mosquito ( Aedes aegypti ) larvae compared to nematode-killed ones [ 169 ]. Tests on the carabid beetle Carabus granulatum , a predator of the lepidopteran host of H. amazonensis , showed that larvae and adults both avoided feeding on infected larvae when they had a choice [ 170 ].…”
Section: Interaction With the Biotic And Abiotic Environmentmentioning
confidence: 99%